IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE POKEMON GO PADA MATA PELAJARAN IPS DI SMP NEGERI 9 MALANG - Wahyuni, Revi; Rosyida, Fatiya (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2024)
Abstract: This research is a qualitative descriptive study, data obtained through observations, interviews and documentation, this research was carried out because social studies learning was carried out during the day, making students feel less enthusiastic about participating in learning, so there is a need for more enjoyable learning so that students actively participate. social studies learning, this research aims to find out how to implement the Pokemon Go type cooperative learning model in social studies subjects at SMP Negeri 9 Malang, the results of this research show the steps for implementing the Pokemon Go type cooperative learning model in social studies subjects at SMP Negeri 9 Malang The planning stage contains preparations before implementing cooperative learning using the Pokemon Go type. In implementing the learning, there are several steps that are carried out, namely the preliminary stage, core and closing activities, and evaluation. Apart from that, there are inhibiting and supporting factors during the activities of implementing the Pokemon Go type cooperative learning model. The obstacles are signal problems, students who do not master the material, and some students who are less active, while the supporting factors are the ease of using devices, the availability of free WiFi and students who are enthusiastic about learning Pokemon Go, and solutions to overcome the problems of implementing the Type Cooperative Learning Model. Pokemon go in social studies subjects at SMP Negeri 9 Malang